Sob o véu da Igreja Católica a serviço dos imigrantes brasileiros nos EUA: políticas de identidade - Silva, Darci Donizetti da (2019)
This thesis is a study about a work developed by the Catholic Church in the United States, more specifically with the Brazilian Immigrant Community in the area of Boston, MA. The major goal is to analyze how politics of identify are present in the work with those communities and how they meet the expectation by the Brazilian immigrant who are members in these communities. The study is based in theoretical reference such as the sintagma metamorphose - identity, emancipation, and the concept of political identities development by Antonio da Costa Ciampa, as well as, other theorists related to Brazilian immigration studies to the USA, such as: Maxime L. Margolis and Ana Cristina Braga Martes. This thesis is organized in four chapters. The first one deals with immigration contextualization process to the USA, challenges and organization forms as well as the kind support provided in the country, if any. Second chapter explains which methodology was chosen for the realization of this study, such as: field diary, interview, life history as well semi - structured interview. This chapter seeks to justify the choosing process for the selection of subjects for this study as well. The third chapter presents the theoretical references. However, the major goal has been to provide a brief and systematic notion of the immigrant in relationship to politics of identity. Forth chapter describes instruments and techniques such as narratives gathering through mans of interviews and illustrations, described here by the researcher field diary ,whose goal is to exam and discuss the existing relationships between the ministry of the American Catholic Church and the immediate reality of Brazilian immigrants, as well as their felt needs. Thus, we have stressed two relevant points, the first one is related to the human and social dimension and the last speaks to the religious aspect, core object of this thesis as a disclosure of a life reality by the Brazilian immigrants in the USA, mediated by its challenges and an analytical views of proposed action of the Catholic Church in America as an attempt to answer the longings and aspirations of such an immigrant population in an ongoing crescendo, as stated by a Brazilian speaker in Florida who said: - “the church is like my mother’s home.”